(3GddHGH aj eYQaI GdCfSGHs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfqj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ , J (B630 (3g`s; (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s ((3jhSa Hf eMeO Hf eaVd Hf eMeO GdCfUGQj GdNRQLj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CMSf cd TF Ndbg hHOC Ndb GdEfSGf ef Wjf s
(3BNQgG (B:s
(3hjfJgj BNQg aj MQa GdNGA , HJQLeI GdNjdGej HbJM GdNGA hSchf GdjGA GdeKfGg ef JMJgG hHYOgG dGe Cda haj BNQgG eje s
(3GfXQ Qbe (B769s
(3Qbe (B1189 (3JGQjNs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs